The Influence of Green Accounting, Environmental Performance, And Share Ownership on Corporate Financial Performance with Corporate Social Responsibility as An Intervening Variable in Basic Industrial and Chemical Sector Companies Listed on the IDX, 2018 – 2022 - Kumalasari, Roro Endah; Roslina, Nita Yura; Alvionita, Tia (Jurnal Computech & Bisnis (e-journal), 2023)
This study aimed to examine and evaluate the impact of Green Accounting, Financial Performance, and Stock Ownership on Corporate Financial Performance (CFP) in the primary and chemical industry sectors of companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. This research also aimed to investigate the role of Corporate Social Responsibility (CSR) as an intervening variable in this relationship. The sample for this study comprised 80 companies operating in the primary and chemical industrial sectors listed on the BEI. The utilization of purposive sampling methodology chose the sample, and the analysis of the data was conducted using Eviews 9 software and Sobel calculations. This study's findings suggest that no statistically significant relationship exists between Green Accounting, Environmental Performance, Stock Ownership, and Corporate Financial Performance. The variable of interest, Corporate Social Responsibility (CSR), exerts a notable influence on the financial performance of corporations. Green Accounting and Environmental Performance variables exhibit a notable influence on Corporate Social Responsibility. However, the variable of Stock Ownership does not demonstrate a substantial impact on Corporate Social Responsibility. In addition, it can be observed that the variables of Green Accounting, Environmental Performance, and Stock Ownership do not exert independent influence on Corporate Financial Performance when mediated by Corporate Social Responsibility.